Letter (copy) : Assistance to Republican Spaniards
1949-04-07 038-0007-001 Secretary's. EK/264. 7th April, 1949. The Lady Layton, Chairman, National Joint Committee for Spanish Relief, 39, Victoria Street, London, S.W.1. Dear Lady Layton, Assistance to Republican Spaniards. In Mr. Tewson's absence from the country I am acknowledging your letter of the 4th instant regarding the work which the National Joint Committee has done and is still doing on behalf of Republican Spaniards. Your letter will be brought to Mr. Tewson's attention upon his return immediately after Easter. Yours faithfully, Private Secretary. 292/946/38/7(I)